Towards Integrated Air Pollution Monitoring and Health Impact Assessment Using Federated Learning A Systematic Review - En Xin Neo; Khairunnisa Hasikin; Mohd Istajib Mokhtar; Khin Wee Lai; Sarah Abdul Razak; Hanee Farzana Hizaddin; Muhammad Mokhzaini Azizan (FRONTIERS, 2024)
Front. Public Health 10:851553